There are no awards for surviving racism, sexism, and ageism in the academy: contemplations of a senior faculty member. Issue 3 (3rd July 2021) - Hendrix, Katherine Grace
ABSTRACT: Nearing the end of my career, this narrative reflects my thoughts entering unknown territory—exiting my postsecondary institution and entering retirement. After a lifetime of working, this piece lays bare my apprehension as I ponder the aging process and the future. Answering the question, "if there are no students, am I still a professor?" while implicitly exploring "am I becoming an old lady?" led me to contemplate my career in academia, including battles for survival and success. Consequently, I have come to a realization of critical magnitude—there are no awards for surviving racism, sexism, and ageism in the academy.